THE USE OF DIGITAL TRANSFORMATION IN THE EDUCATIONAL PROCESS OF THE UNIVERSITY - Zhakupova Galina Spataevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article shows the role and place of the modern information environment in the education and upbringing of university students, emphasizes that education is aimed at the formation of a person as a person, his attitude to the world, society, people. Therefore, it is important to use electronik educational resources correctly in the process of education.